1990
DOI: 10.1084/jem.171.4.1189
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor V beta gene usage in a human alloreactive response. Shared structural features among HLA-B27-specific T cell clones.

Abstract: A strategy, based on using V beta family-specific oligonucleotides, was developed for specific amplification and direct sequencing of human TCR V beta genes. With this strategy, it was possible to undertake a structural analysis of TCRs from human T cell clones in specific responses. 12 HLA-B27-specific cytotoxic clones were examined. The results reveal a nonrandom use of V beta gene diversity in this alloreactive response in that: (a) the clones express a restricted number of V beta segments, including a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 45 publications
(61 reference statements)
3
18
0
Order By: Relevance
“…4850 Spectratyping, which examined distribution of CDR3 lengths within each V-Jβ family 51 , suggested the activation of many TCRs, with a near-Gaussian distribution among multiple Vβ families in human and rat cells responding in MLRs, 52 consistent with previous studies focusing on smaller, more targeted alloreactive populations 53 . Thus, it was surmised that the alloreactive repertoire is highly diverse.…”
Section: On the Origin And Diversity Of Alloreactive T Cellssupporting
confidence: 84%
“…4850 Spectratyping, which examined distribution of CDR3 lengths within each V-Jβ family 51 , suggested the activation of many TCRs, with a near-Gaussian distribution among multiple Vβ families in human and rat cells responding in MLRs, 52 consistent with previous studies focusing on smaller, more targeted alloreactive populations 53 . Thus, it was surmised that the alloreactive repertoire is highly diverse.…”
Section: On the Origin And Diversity Of Alloreactive T Cellssupporting
confidence: 84%
“…Increasing numbers of studies have reported on restricted TCR ~ usage in various diseases, such as experimental allergic encephalomyelitis [1,42], allograft rejection [6,23], multiple sclerosis [29], Grave's disease [11,38], sarcoidosis [26], primary biliary cirrhosis [25], Crohn's disease [31] and choriomeningitis [41]. It is also well known that TCR V gene usage is restricted in human T cells stimulated with superantigen [8,20] as well as in TIL of melanoma and glial tumours [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, Yersinia-specific B27restricted CTL preferentially used Vp13.3 and 14, autoreactive B27-restricted CTL preferred V p 13.2 and 17 (21). Interestingly, Vp gene segments 13, 14 and 17 show high sequence homologies; these TCR Vp families have also been shown to be expressed in HLA-B27-alloreactive CTL (22).…”
Section: Enterobacterial Antigens With Tropism For Joint Structuresmentioning
confidence: 96%